2012
DOI: 10.1186/gm329
|View full text |Cite
|
Sign up to set email alerts
|

Genetic determinants of metabolism in health and disease: from biochemical genetics to genome-wide associations

Abstract: Increasingly sophisticated measurement technologies have allowed the fields of metabolomics and genomics to identify, in parallel, risk factors of disease; predict drug metabolism; and study metabolic and genetic diversity in large human populations. Yet the complementarity of these fields and the utility of studying genes and metabolites together is belied by the frequent separate, parallel applications of genomic and metabolomic analysis. Early attempts at identifying co-variation and interaction between gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 102 publications
1
15
0
Order By: Relevance
“…The parallel development of biobanking and high-throughput sequencing, genotyping and phenotyping technologies has enabled a new generation of successful molecular epidemiology studies, such as genome-wide association studies (GWAS) [1], metabolome-wide association studies (MWAS) [2,3] and even metabolomics GWASes [4,5,6]. It currently provides a wide range of new opportunities for the development of biomarkers of medical interest with current applications in toxicology [7], cancer [8,9,10], cardiovascular disease [11,12], prediction of treatment outcomes [13,14,15] or “pharmacometabonomics” [16,17], and more recently metabolic modelling of the patient journey in a clinical environment [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The parallel development of biobanking and high-throughput sequencing, genotyping and phenotyping technologies has enabled a new generation of successful molecular epidemiology studies, such as genome-wide association studies (GWAS) [1], metabolome-wide association studies (MWAS) [2,3] and even metabolomics GWASes [4,5,6]. It currently provides a wide range of new opportunities for the development of biomarkers of medical interest with current applications in toxicology [7], cancer [8,9,10], cardiovascular disease [11,12], prediction of treatment outcomes [13,14,15] or “pharmacometabonomics” [16,17], and more recently metabolic modelling of the patient journey in a clinical environment [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…hagsc.org/hgdp/), 1000 Genomes Projects (Durbin et al 2010), and every published whole-genome sequence [references in (Olson 2012)] demonstrated that individuals are genetically unique. Metabolomic, proteomic, and clinical data also demonstrate biochemical individuality (Williams 1956;Robinette et al 2012). Adj p value = corrected for multiple comparisons…”
Section: Experimental Design and Main Resultsmentioning
confidence: 99%
“…Thousands of GWA studies have been published associating one or more single nucleotide variants to ~800 phenotypes that include disease [106], diet intake [94], metabolism [8, 81], anthropometry [106], pharmacogenomics [17, 70], and brain-related disorders [56]. Over 15,000 trait–SNP associations at p value ≤5.0 × 10 −8 have been amassed as of 2013 ([106] and https://www.ebi.ac.uk/gwas/).…”
Section: Guidelines Standards and Reproducibility Of Scientific Datmentioning
confidence: 99%